PEMODELAN FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS PEMBANGUNAN MANUSIA DI SUMATERA UTARA MENGGUNAKAN REGRESI SPASIAL - Asmita Tumanggor; Elmanani Simamora (Lembaga Pengembangan Kinerja Dosen, 2023)
The quality of life in North Sumatra currently still needs improvement, where poverty rates and human development are still lagging. These problems can be reflected in the community welfare indicator, namely the Human Development Index (IPM). One of these problems can be solved by knowing the factors that determine the Human Development Index in North Sumatra. The Human Development Index is suspected to contain elements of spatial dependency, therefore in this study the spatial regression method will be used with a spatially dependent effect model. The results of the analysis and discussion obtained are that the SAR model is the appropriate model in the case of the Human Development Index in North Sumatra. Predictor variables that significantly influence the Human Development Index in North Sumatra are Pure Enrollment Rate (APM) at Senior High School level , Poverty Rate , Open Unemployment Rate , and PDRB on the basis of price .